Selection of pasture cultivars from many germplasm entries under grazing - Grof, Bert (International Center for Tropical Agriculture, 1993)
Grassland improvement work, particularly in the early stages of developing a program for tropical regions, involves a comparison of new accessions selected from wild populations whose potential as cultivated forages is often unknown. Pasture species evaluation strategies employed at CIAT's main savanna research station in the Colombian Eastern Plains (Llanos Orientales) and appropriate techniques for testing large numbers of accessions under grazing are discussed. During the 1977-1982 period, 41 accessions of 14 leguminous species and seven grass species have been screened with the techniques described. Results of preliminary grazing tests of Centrosema spp., Desmodium ovalifolium, and Stylosanthes capitata are reported.